Laying the foundations : manual of the British Museum Iraq Scheme archaeological training programme - MacGinnis, John; Rey, Sébastien (2022)
This title, which developed out of the British Museum's 'Iraq Scheme' archaeological training programme, covers the core components for putting together and running an archaeological field programme. While the manual is oriented to the archaeology of Iraq, the approaches are no less applicable to the Middle East more widely.